A Bayesian network approach to investigating climate change and commodity price change impacts on human well-being: a case study of employment from Queensland, Australia - Lynam, Timothy (Wiley, 2012)
This book reports the current state of knowledge on climate change adaptation, and seeks to expose and debate key issues in adaptation research and practice. The book is based on key contributions from the First International Conference on Climate Change Adaptation ‘Climate Adaptation Futures’, held on the Gold Coast, Australia, in June 2010. That three-day meeting of over 1000 researchers and practitioners in adaptation from 50 countries and was the first of its kind. Part 8: Urban infrastructure and livelihoods - 31. A Bayesian network approach to investigating climate change and commodity price change impacts on human well-being: a case study of employment from Queensland, Australia T. Lynam, J. Langridge, A. Langston and Y. Maru
Climate Adaptation Futures
Keywords: Housing, communities and neighbourhoods; Housing, community and neighbourhoods